Production Performance of Peking Ducks with Feeding of Fermented Yeast Culture Pineapple Peel (Saccharomyces cereviceae) - Bulkaini Bulkaini; Djoko Kisworo; Budi Indarsih; I K Sumadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Poultry production performance is reflected by body weight gain, ration conversion and carcass percentage. This study was conducted with the aim of knowing the optimum level of use of fermented pineapple peel in the ration on production performance and carcass percentage of male Peking ducks. The research material was male Peking duck aged 3 weeks with initial body weight of 343.90 ÃÂ± 0.90 g. 240 male Peking ducks were placed randomly in battery cages based on a Completely Randomized Design with 6 treatments and 5 replications, namely P0=ration without fermented pineapple peel (FPP); P1=the ration contains 5% FPP; P2=ration contains 10% FPP; P3=the ration contains 15% FPP; P4= ration contains 20% FPP and P5=the ration contains 25% FPP.ÃÂ Based on One way ANOVA analysis and Duncan's test, it was found that the use of fermented pineapple peel 10% significantly (P<0.05) increased the final body weight (1.693g/head), body weight gain (1.350 g/head), and carcass percentage (55.25%). From the results of the study, it can be concluded that the optimum level of use of fermented pineapple peel with yeast culture on body weight gain, slaughter weight, carcass weight and carcass percentage, respectively: 8.80%; 8.40%; 7.25% and 9.50%.